Сравнение электрофизических характеристик различных комбинаций полипропиленово-полиэтилентерефталатного диэлектрика, пропитанного трансформаторным маслом Т-1500 и полиметилсилоксановой жидкостью ПМС-20 - Гунько, Виктор Иванович; Дмитришин, Алексей Ярославович; Топоров, Сергей Олегович; Танасова, Елена Дмитриевна; Фещук, Татьяна Анатольевна (НТУ "ХПИ", 2018)
Рассмотрены результаты исследований электрофизических характеристик различных комбинаций пропитанного полипропиленово-полиэтилентерефталатного диэлектрика, который может быть применен в качестве рабочего диэлектрика секций высоковольтных импульсных конденсаторов. На основе проведенных экспериментов на макетах секций конденсатора проанализировано влияние полярности диэлектрика и обкладок секции на электрическое сопротивление изоляции и кратковременную электрическую прочность таких диэлектрических систем.

Results of researches of the electrical characteristics of various combinations of the impregnated dielectric on base of polypropylene (PP) and polyethylene terephthalate (PET) films, which can be applied as working insulator of high-voltage pulse capacitor’s sections, are reviewed. On the basis of experiments on mockups of the capacitor sections influence of the polarity of the films and capacitor plates, affecting the electrical insulation resistance and short-term dielectric strength of such dielectric systems, is analyzed. It is found that the structure of PET + PP + PET and PET + PET + PP has the highest dielectric strength, and they can be recommended as working dielectric. As to impregnation liquids, it is found that the choice depends on the ambient temperature. Also for charge-discharge repetition rate larger than 0.1 Hz, is recommended dielectric structure with an increased non-polar component content
Comparison of electrophysical characteristics of various combinations of polypropylene-polyethylene terephthalate dielectric impregnated with transformer oil T-1500 and polymethylsiloxane liquid PMS-20
Keywords: пленочный диэлектрик; полярность диэлектрика; электрическое сопротивление изоляции; электрическая прочность; высоковольтный импульсный конденсатор; film dielectric; dielectric polarity; dielectric strength